SUPERVISION ON MAYANG NATURAL ATTRACTIONS FOR THE 2021-2022 PERIOD (COVID-19 TRANSITION PERIOD) IN PEKANBARU CITY - Nurul Fitirah; Harapan Tua RFS (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2023)
To determine whether a task or activity is being carried out as it should be, the supervisor engages in various actions to gather information and make evaluations. During the Covid-19 pandemic, it is important to supervise directly by related parties to overcome the spread of the corona virus which is currently rampant. Supervision on the Alam Mayang tourist attraction is supervised by the Pekanbaru City Culture and Tourism Office and the Covid- 19 Task Force. However, there are many obstacles that become obstacles in carrying out supervision on tourist attractions. The purpose of this study is to see how the supervision carried out by the Pekanbaru City Culture and Tourism Office in supervising tourist attractions during the Covid-19 pandemic and to see what factors are hindering the Supervision process. This research was located in Alam Mayang using qualitative descriptive methods, and data collection techniques through observation, interviews and documentation. The results of this study are said to have not been maximized, this is due to the lack of responsiveness of the Department in preventing Covid-19 and also the lack of awareness from visitors because they do not comply with health protocols.